2014
DOI: 10.1590/s1679-45082014rc2860
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D intoxication: case report

Abstract: Hypervitaminosis D is a rarely reported condition. In general it is only perceived when hypercalcemia is not resolved. The use of vitamin D has increased in recent years because of its benefits, but as a result, intoxication cases have occurred more frequently. This report describes a patient who presented worsening of renal function and hypercalcemia. After investigation, vitamin D intoxication was confirmed and it was due to an error in compounding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 9 publications
0
10
0
2
Order By: Relevance
“…Seven paediatric cases of hypercalcaemia due to vitamin D intoxication were reported in association with a fish oil supplement, where the stated dose was roughly 4000 times less than the actual dose [31]; in one of these cases, an infant in whom the stated daily dose was 2000 IU day -1 was actually taking 6000 IU day -1 [30]. Toxicity associated with inaccurately manufactured and labelled vitamin D supplements is a globally reported problem [32,[34][35][36][37][38][39][40][41][42][43]. To our knowledge, such errant labelling has not been reported in conjunction with licensed formulations.…”
Section: Causes Of Vitamin D Toxicitymentioning
confidence: 99%
“…Seven paediatric cases of hypercalcaemia due to vitamin D intoxication were reported in association with a fish oil supplement, where the stated dose was roughly 4000 times less than the actual dose [31]; in one of these cases, an infant in whom the stated daily dose was 2000 IU day -1 was actually taking 6000 IU day -1 [30]. Toxicity associated with inaccurately manufactured and labelled vitamin D supplements is a globally reported problem [32,[34][35][36][37][38][39][40][41][42][43]. To our knowledge, such errant labelling has not been reported in conjunction with licensed formulations.…”
Section: Causes Of Vitamin D Toxicitymentioning
confidence: 99%
“…The daily intake of 100,000 IU or more could cause VD toxicity ( 68 ), while an increased intake of up to 2000 fold against the prescribed dosage could lead to renal failure ( 82 ). It has also been reported that an annual treatment of 500,000 IU VD 3 increases fracture risk ( 83 , 84 ).…”
Section: Limitations Of the Use Of Vitamin D As Therapeuticsmentioning
confidence: 99%
“…Hypercalcaemia has many causes; more than 90% of cases result from primary hyperthyroidism or malignancy 1. Other causes of hypercalcaemia include chronic lithium therapy, thiazide diuretics, pheochromocytoma, adrenal insufficiency, theophylline toxicity and vitamin D poisoning,2 and there was a fatal case of hypercalcaemia due to calcium channel blocker ingestion. In general, treatment of hypercalcaemia is aimed at lowering serum calcium levels.…”
Section: Descriptionmentioning
confidence: 99%